(untitled) (Raparin Journal of Humanities (RJH), 2024)
Our research entitled (The Method of Russian Orientalists for Research in Kurdish Literature) is an attempt to study the critical method they have followed for research in Kurdish literature. In this study we want to answer several questions: What was the research method of these orientalists for Kurdish literature? What are the scientific values of research methods? What is the significance of these studies for the history of Kurdish literature? Our study consists of two main parts. The first part, entitled Origin and History of Orientalism, consists of three topics. First topic; what is orientalism? It is an attempt to interpret the terms and concepts of Orientalism. The second topic is entitled History and Development of Orientalism. In this section we have interpreted the history of orientalism emergence. This section is a theoretical section. The second part is called the Method of Russian Orientalists. It consists of two topics. The first topic is the identification of the research methods of Russian orientalists, and the second topic is the scientific value of these methods. This practical section exemplifies the research of orientalists such as Abkarovich Urbili, E. A. Smirnova, Zare Osb, E. Yi Vasilyeva, M. S. Lazarev, M. B. Rodinko, and Alexander Zhaba. Finally, the results of our research are defined in several points, with a list of sources according to the Harvard system.